Literature Study: Global Financial Crisis and Islamic Finance As A Solution - Dedy Dwi Arseto; Nirmadarningsih Hiya; M. Sabri Abd. Majid; Marliyah Marliyah; Rita Handayani (STIE Trisna Negara OKU Timur, 2022)
Literature Study: Global Financial Crisis and Islamic Finance As A Solution. One of the basic tenets of Islamic finance is